Dampak Keterampilan Teknis pada Employability Skills Siswa di Era Industri Kreatif: The Impact of Technical Skills on Students' Employability Skills in the Creative Industry Era - Mulifah Mulifah; Lilik Anifah; I Gusti Putu Asto Budi Tjahjanto (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2024)
The creative industry era has changed the global economic landscape, creating new opportunities and challenges for graduates of Visual Communication Design (DKV). This study aims to analyze the impact of technical skills on the employability of DKV students in Indonesia in the context of the rapidly growing creative industry. Using a descriptive quantitative approach, a survey was conducted on 412 respondents, consisting of final-year students and new alumni of the DKV Expertise Concentration. The results showed a significant positive correlation between technical skills and employability skills (r = 0.68, p < 0.001), with technical skills predicting 43% of the variance in employability skills. Further analysis revealed that the most significant gaps were adapting to new technologies and project management, which are essential for today's workforce. In addition, UI/UX design, data visualization, and interactive digital content were identified as the industry's most needed technical skill areas. This study emphasizes the importance of developing a DKV curriculum that balances technical and soft skills, such as communication, collaboration, and problem-solving, to improve graduates' readiness to face the demands of the creative industry era. The implications of this research include the need for curriculum updates responsive to industry trends, strengthening cooperation between educational institutions and industry, and developing more effective transition programs from campus to the world of work.